Research on the application of artificial intelligence in the field of enterprise financial management and strategic decision-making - Wang, Miao; Dai, Jianhua (Edelweiss Applied Science and Technology, 2025)
This study explores the integration of artificial intelligence into enterprise financial management and strategic decision-making, identifying key combination points and application mechanisms. The research outlines artificial intelligence development trends and analyzes existing applications in human resource and accounting management to examine potential integration pathways in enterprise financial management. The study reveals that artificial intelligence enhances financial management through big data platforms that enable data collection, mining, and visualization. AI facilitates enterprise internal management innovation, particularly in human resource management, and provides quantitative support for strategic decision-making. Artificial intelligence transforms traditional financial management by providing intuitive data visualization, generating strategic insights, and reducing decision-making risks. The integration requires a paradigm shift in both technology and management mindset, with continued human oversight remaining essential. Enterprises should gradually introduce artificial intelligence into financial management and strategic processes, focusing on building AI teams and robust data governance frameworks while avoiding over-reliance on short-term benefits. Financial professionals need to develop new competencies to effectively collaborate with AI systems.